Method for preparing battery-grade lithium carbonate from waste lithium batteries

By combining the choline chloride-citric acid low eutectic solvent and activated carbon, the problems of low lithium ion recovery rate and low lithium carbonate purity in lithium iron phosphate batteries were solved, an efficient and simplified lithium ion recovery and purification process was achieved, and high-purity lithium carbonate was prepared.

CN120757132APending Publication Date: 2025-10-10JIANGSU UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510994354.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-18
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

In the existing technology, the lithium ion recovery rate in lithium iron phosphate batteries is low, the process is complicated, the lithium carbonate purity is low, the crystal particle size is large, the particle size is uneven, and there are many impurities, which leads to resource waste and environmental pollution.

Method used

A choline chloride-citric acid low eutectic solvent system is used to accelerate lithium ion leaching by selectively complexing lithium ions and adding a polymer catalyst. Combined with deep impurity removal using activated carbon, gradient cooling crystallization and three-stage purification and beating processes are used to control crystallization kinetics and improve lithium ion recovery rate and purity.

Benefits of technology

The recovery rate and purity of lithium ions are significantly improved, the impurity content is reduced, the preparation of high-purity battery-grade lithium carbonate is achieved, the process flow is simplified and the preparation time is shortened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120757132A_ABST
    Figure CN120757132A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium battery materials, in particular to a method for preparing battery-grade lithium carbonate from waste lithium batteries. The method comprises the following steps: disassembling, crushing and sieving a recycled lithium iron phosphate battery to obtain a crushed lithium battery material; a choline chloride-citric acid mixed solution is adopted to conduct leaching treatment on the crushed materials, and sulfuric acid is added to inhibit leaching of iron and phosphorus ions; filtering to obtain a first filtrate and a first filter residue; adding calcium hydroxide into the first filtrate, and filtering to obtain second filtrate and second filter residues; adsorbing the second filtrate with activated carbon to remove impurities, and filtering to obtain a third filtrate and a third filter residue; adding hydrochloric acid into the third filtrate to obtain a lithium chloride solution; carbonizing and converting the lithium chloride solution into a lithium carbonate solution; and carrying out gradient crystallization treatment on the lithium carbonate solution, pulping with pure water, and drying to obtain the high-purity lithium carbonate finished product. The method overcomes the problems of low lithium recovery rate, complex process, low lithium carbonate purity, large crystal particle size, more impurities and the like of the existing lithium iron phosphate battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium battery material waste treatment, and in particular to a method for preparing battery-grade lithium carbonate from waste lithium batteries. Background Art

[0002] With the rapid development of the new energy vehicle industry, my country has become the world's largest consumer of lithium batteries. By 2025, retired lithium iron phosphate batteries are expected to reach 780,000 tons, containing approximately 3.5% lithium. Failure to effectively recycle these batteries will not only waste resources but also pollute the environment. Furthermore, battery-grade lithium carbonate, a key raw material for producing cathode materials such as LiFePO4 and LiCoO2, must meet stringent standards of 99.5% purity and ≤200 ppm of impurity ions.

[0003] However, current technology faces key challenges: Lithium ions in lithium iron phosphate batteries are stably stored within the LiFePO4 lattice structure, resulting in inefficient and time-consuming leaching. The recovery process is complex, leading to significant lithium loss. The final product, lithium carbonate, suffers from widespread issues such as insufficient purity, coarse crystal size, and a yellowish appearance. Furthermore, high process costs and low overall lithium recovery rates severely restrict the economic viability and feasibility of recycling. Summary of the Invention

[0004] The present application provides a method for preparing battery-grade lithium carbonate from waste lithium batteries to solve technical problems such as low lithium ion recovery rate of lithium iron phosphate batteries, complex process, low lithium carbonate purity, large crystal particle size, uneven particle size, and many impurities.

[0005] The first embodiment of the present application provides a method for preparing battery-grade lithium carbonate from waste lithium batteries, comprising the following steps:

[0006] (1) Disassembling, crushing, and screening the recovered lithium iron phosphate batteries to obtain battery scraps;

[0007] (2) preparing a mixed solution of choline chloride and 5%-20% citric acid solution in a molar ratio of 1:1, leaching the battery crushed material, and reacting the mixed solution with the mixed solution in a solid-liquid ratio of 1:2-5, while adding 5-10 wt / % polymer powder catalyst to obtain a first filtrate and a first filter residue;

[0008] (3) adding calcium hydroxide to the first filtrate to adjust the pH to 4-6 to precipitate iron ions and phosphorus ions, and filtering to obtain a second filtrate and a second filter residue;

[0009] (4) adding 0.1-0.5 wt / % activated carbon to the second filtrate to reduce the residual iron, phosphorus and other impurities in the solution to less than 1 mg / L, and filtering to obtain a third filtrate and a third filter residue;

[0010] (5) adding hydrochloric acid to the third filtrate to adjust the pH to 1.0-2.0, the reaction temperature is 20-60° C., and the reaction time is 2-4 h to obtain a lithium chloride solution;

[0011] (6) adding 1-5 wt / % of a catalyst to the lithium chloride solution, the reaction temperature is 60-80° C., and carbon dioxide is introduced into the lithium chloride solution at a ventilation rate of 0.05-0.1 liter / minute, a pressure of 6.5 MPa, and a reaction time of 18-23 hours to obtain a lithium carbonate solution;

[0012] (7) The lithium carbonate solution is heated to 80-100°C and kept warm for 1 hour, and then cooled in a gradient manner and kept warm for 1-2 hours, wherein the gradient cooling is 20°C per stage, and filtered to obtain a fourth filtrate and a fourth filter cake, and the fourth filtrate is recycled according to step (6), and the fourth filter cake is pulped 3 times at a pulping temperature of 60-80°C, and filtered to obtain a high-purity lithium carbonate wet product, which is dried at 100-120°C to obtain a high-purity lithium carbonate crystal powder.

[0013] It is understandable that the embodiment of the present application significantly improves the efficiency of lithium ion selective leaching and suppresses the dissolution of impurity metals by adding a choline chloride-citric acid mixed solution and a distribution adjustment strategy of first alkali and then acid by adding a polymer powder catalyst. By activated carbon adsorption decolorization and deep impurity removal, the cleanliness of the solution is effectively improved, the residual metal impurity ions are reduced, and the whiteness of the final product is improved. The purified lithium ions are prepared into a lithium chloride solution, and a fine-particle lithium carbonate precursor is generated through a controllable carbonization reaction. The lithium carbonate slurry is subjected to gradient cooling and crystallization, combined with high-purity water beating and washing to achieve gradient removal of impurity ions, and finally a high-purity battery-grade lithium carbonate product is obtained.

[0014] Furthermore, in step (2), the reaction temperature is 60-80° C., the reaction time is 2-7 hours, and sulfuric acid is added after the reaction to adjust the pH to 1.0-2.0.

[0015] Furthermore, the polymer powder catalyst is one of polycarbonate, polyethylene terephthalate or polyamide.

[0016] It can be understood that the embodiments of the present application, by adding a polymer powder catalyst, generate a local electric field through the triboelectric effect, thereby accelerating the separation of lithium ions from the LiFePO4 lattice.

[0017] Furthermore, in step (4), the reaction temperature is 40-60° C., and the reaction time is 1-3 h.

[0018] Furthermore, the catalyst is one of triethylamine or tripropylamine.

[0019] Furthermore, during step (7), the stirring speed is controlled at 300-600 r / min.

[0020] It can be understood that the embodiments of the present application, by controlling the stirring speed at 300-600 r / min, are conducive to maintaining a suitable saturation concentration, reducing impurity inclusion, promoting solute diffusion, and optimizing crystal morphology.

[0021] Furthermore, in the step (1), the sieve is sieved through a 100-200 mesh sieve.

[0022] Furthermore, the iron and phosphorus contents in the first filtrate are 1 eq, and the amount of calcium hydroxide added is 1.5-2.0 eq.

[0023] Furthermore, in step (7), pure water with a particle number of ≤1 / mL is used for beating.

[0024] It can be understood that the embodiments of the present application avoid the introduction of additional ions and organic impurities by using pure water for pulping, thereby improving the purity of the finished product.

[0025] Furthermore, the drying of the wet lithium carbonate product in step (7) needs to be carried out under negative pressure.

[0026] Beneficial effects:

[0027] (1) The present invention adopts a choline chloride-citric acid eutectic solvent system, wherein choline chloride acts as a hydrogen bond acceptor and citric acid acts as a hydrogen bond donor. After mixing in a molar ratio, the mixture is heated at 60-80°C to form a transparent liquid with a stable hydrogen bond network. Water is added to reduce the viscosity of the system to improve the mass transfer efficiency. During the selective leaching process, chloride ions and lithium ions form a soluble complex, lithium chloride, to achieve directional dissolution of lithium. At the same time, citric acid provides hydrogen ions to dissolve metal oxides and reduce high-valent metals through carboxyl groups. Chloride ions preferentially coordinate lithium ions rather than sodium ions and potassium ions, further enhancing the selectivity and improving the leaching rate of lithium ions. The acid treatment stage activates lithium leaching and maintains a reducing environment. At low pH, citric acid preferentially precipitates trivalent iron ions, while lithium ions remain in the liquid phase due to lithium chloride complexation. A polymer catalyst is added, and amino and carboxyl groups adsorb lithium ions and accelerate electron transfer to promote the breaking of Li-O bonds in lithium iron phosphate. The surface negative charge repels high charge density ions and selectively enriches lithium ions, further improving the leaching rate of lithium iron phosphate lithium ions.

[0028] (2) During the gradient cooling crystallization process, the filtrate obtained by filtration still dissolves a small amount of lithium ions due to the reverse solubility characteristics of lithium carbonate. This filtrate can be circulated to the initial crystallization stage of step (6) to participate in crystallization again, thereby reducing the loss of lithium carbonate yield and improving the recovery rate of lithium ions. During the three purification beating processes, the first beating filtrate is circulated to the gradient cooling crystallization mother liquor system, and its low ion concentration characteristics are used to promote the diffusion of impurities between crystals; the second beating filtrate is circulated to the first beating unit as a dilution medium, and the third beating filtrate is circulated to the second beating unit, and fresh pure water is reduced by cascade reuse of the filtrate; the three beating washing waters are mixed and reused for the first beating, forming a closed water cycle, and simultaneously achieving an improvement in the lithium ion recovery rate;

[0029] (3) The activated carbon of the present invention achieves efficient adsorption, decolorization and deep impurity removal by virtue of its developed pore system composed of microcrystalline carbon: the micropores account for more than 95%, and small molecular pigments and ions are adsorbed by van der Waals forces; the oxygen-containing functional groups on the surface of the activated carbon give polarity, and selectively complex metal ions by chemical adsorption or ion exchange, thereby deeply removing residual impurity ions such as sodium ions and phosphate ions, while the lithium chloride complex formed by chloride ions and lithium ions mainly remains in the liquid phase due to the size effect, and the metal ion residue is <20ppm;

[0030] (4) The present invention precisely controls the crystallization kinetics through three stages. In the high-temperature stage (80–90°C), spontaneous nucleation is suppressed, the solution is in a metastable state, and a uniform solute environment is provided. In the medium-temperature stage (25–50°C), the temperature is slowly lowered to induce secondary nucleation, forming controllable seed crystals and avoiding impurity encapsulation caused by explosive nucleation. In the low-temperature stage (0 to –20°C), small crystals are dissolved and redeposited on large crystals. Sodium ions, magnesium ions, and other ions have high solubility at low temperatures, while the solubility of lithium carbonate increases significantly with decreasing temperature, thereby achieving separation of lithium and alkali metals and reducing impurities. High-purity water beating uses a triple mechanism to deeply remove impurities: ion diffusion - low ion concentration forms a concentration gradient, driving the residual sodium ions and potassium ions between the crystals to diffuse into the water phase. After a single wash, the sodium ion content is less than 20ppm. Sulfate ions are desorbed from the crystal surface through the Stokes-Einstein diffusion principle, and the residual sulfate ions are less than 20ppm. Colloidal stripping - destroys the hydrogen bonds and electrostatic adsorption between colloids such as iron hydroxide and crystals, and mechanical desorption is achieved with 300r / min stirring to remove iron ions.

[0031] (5) In the present invention, lithium ions and hydrochloric acid react to generate lithium chloride solution through proton exchange reaction, and this process forms soluble salts; triethylamine as an organic base catalyst improves the reaction efficiency through a dual mechanism: alkalinity is enhanced, and the ammonium salt is combined to increase the pH of the system, promoting the dissolution equilibrium of carbon dioxide and phase transfer catalysis; the high pressure of 6.5MPa is used to significantly increase the partial pressure of carbon dioxide, and according to Henry's law, the gas solubility increases linearly, and the concentration of liquid carbon dioxide is increased; in the carbonization process, triethylamine continuously consumes hydrogen ions to push the carbonate fractionation equilibrium to the right, which significantly increases the concentration of carbonate ions. The reaction temperature is controlled at 60–80°C to balance kinetic and thermodynamic requirements. The lower limit of 60°C is higher than the CO2 hydration activation energy to ensure the reaction rate, and the upper limit of 80°C is lower than the lithium carbonate solubility inflection point to prevent crystal dissolution. The reaction time of 18–23 hours ensures that the crystals achieve uniform particle size through Ostwald ripening, reducing the particle size of lithium carbonate.

[0032] (6) The present invention adopts a choline chloride-citric acid low eutectic solvent system to efficiently leach lithium ions, while reducing the dissolution of other metal ions, and further simplifies the steps by combining with activated carbon adsorption to remove impurities; in the carbonization crystallization stage, based on lithium chloride solution, triethylamine is added as a reaction promoter, and the reaction is carried out under a high pressure of 6.5MPa and 60-80℃ for 18-23 hours, thereby promoting the nucleation of lithium carbonate by increasing the solubility of carbon dioxide, and forming crystals with a D50 of less than 10 microns through Ostwald ripening; subsequently, by step-by-step cooling crystallization combined with three purification beating processes, the gradient cooling crystallization filtrate is returned to the initial crystallization step, thereby improving the lithium ion recovery rate, and the primary filtrate in the three purification beatings is incorporated into the crystallization mother liquor, the secondary filtrate is returned to the primary beating, and the tertiary filtrate is returned to the secondary beating, thereby realizing the maximum recovery of lithium ions. Finally, while simplifying the overall process flow, the lithium carbonate preparation time is effectively shortened, and the product purity and lithium recovery rate are improved.

[0033] This solves the technical problems of low lithium ion recovery rate of lithium iron phosphate batteries, complex process, low purity of lithium carbonate, large crystal particle size, uneven particle size, and many impurities. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0035] Figure 1 A process flow chart for a method for preparing battery-grade lithium carbonate from waste lithium batteries;

[0036] Figure 2A diagram of a finished lithium carbonate product according to a method for preparing battery-grade lithium carbonate from waste lithium batteries provided in an embodiment of the present application;

[0037] Figure 3 The clarified filtrate after decolorization by activated carbon adsorption in the method for preparing battery-grade lithium carbonate from waste lithium batteries provided in an embodiment of the present application;

[0038] Figure 4 Lithium carbonate crystals according to a method for preparing battery-grade lithium carbonate from waste lithium batteries provided in an embodiment of the present application. DETAILED DESCRIPTION

[0039] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0040] The choline chloride used in the examples of the present application is sourced from Jinan World Chemical Co., Ltd.; the citric acid used is sourced from Shanghai Aladdin Biochemical Technology Co., Ltd.; the calcium hydroxide used is sourced from Nantong Runfeng Petrochemical Co., Ltd.; the triethylamine used is sourced from Jiangsu Runfeng Synthetic Technology Co., Ltd.; the tripropylamine used is sourced from Shanghai McLean Biochemical Technology Co., Ltd.; the polycarbonate used is sourced from Shanghai McLean Biochemical Technology Co., Ltd.; the activated carbon used is sourced from Shanghai Yien Chemical Technology Co., Ltd.; the polyethylene terephthalate used is sourced from Shanghai Haohong Biomedicine Technology Co., Ltd.; the polyamide used is sourced from Shanghai McLean Biochemical Technology Co., Ltd.; the sulfuric acid used is sourced from Nanjing Shengqinghe Chemical Co., Ltd.; the hydrochloric acid used is sourced from Hubei Zhongshui Chemical Co., Ltd.; and the pure water used is sourced from Shanghai Haohong Biomedicine Technology Co., Ltd.

[0041] The following will describe a method for preparing battery-grade lithium carbonate from waste lithium batteries of the present application in combination with examples, in order to solve the technical problems of low purity and large particle size of lithium carbonate of lithium iron phosphate batteries mentioned in the above background technology. The present application provides a method for preparing battery-grade lithium carbonate from waste lithium batteries, in which choline chloride-citric acid is used as a low eutectic solvent system, chloride ions selectively complex lithium ions to form soluble lithium chloride to achieve directional leaching of lithium, while citric acid provides hydrogen ions to dissolve metal oxides and reduce high-valent metals through carboxyl groups, precipitating trivalent iron ions at low pH while lithium remains in the liquid phase, while polymer catalysts accelerate the breakage of Li-O bonds and selectively enrich lithium ions, thereby improving the recovery rate of lithium; simultaneously, activated carbon is used for deep impurity removal: the microporous structure adsorbs small molecular impurities, and the surface functional groups remove sodium ions, phosphate ions and the like by chemical adsorption, and lithium chloride remains in the liquid phase due to the size effect, thereby transferring to the decarbonization step; in the carbonization step, the lithium chloride solution is heated at 6.5 MPa. Under high pressure, triethylamine catalyzes CO2 solubility and complexes magnesium / calcium ions to suppress impurities. The reaction is carried out at 60-80°C for 18-23 hours, allowing carbonate ions to combine with lithium to form lithium carbonate. Crystal growth achieves uniform particle size, resulting in high-purity lithium carbonate with a sodium residue of <20 ppm. The gradient crystallization process uses three-stage temperature control (80-100°C for nucleation suppression, 40-60°C for seed induction, and 0-20°C for dissolving small crystals to separate alkali metals). The filtrate is recycled to the initial crystallization to reduce lithium yield loss and improve lithium recovery. The filtrate from the three beatings is recycled in stages and added to the crystallization mother liquor as a dilution medium. The pure water beating step further reduces the impurity content in the finished lithium carbonate product through concentration gradient diffusion, colloidal stripping, and physical diffusion for deep impurity removal. This solves the technical problems of low lithium ion recovery rate, complex process, low lithium carbonate purity, large crystal particle size, uneven particle size, and high impurity content in lithium iron phosphate batteries.

[0042] Specifically, Figure 1 A schematic flow chart of a method for preparing battery-grade lithium carbonate from waste lithium batteries provided in an embodiment of the present application.

[0043] like Figure 1 As shown, the method for preparing battery-grade lithium carbonate from waste lithium batteries comprises the following steps:

[0044] In step S101, the recycled lithium iron phosphate batteries are disassembled, crushed, and sieved to obtain battery scraps.

[0045] Among them, disassembly can be the automated equipment physically breaking down the battery into smaller components, crushing can be the crushing of the disassembled battery components into smaller particles, and screening can be the separation and grading of the crushed materials according to particle size.

[0046] It is understood that the embodiments of the present application ensure safety by disassembling and separating the battery casing and battery cell components, while also addressing potential hazards and rendering the material crushable. Crushing then reduces the material size to facilitate subsequent sorting and extraction. Using a screen or vibrating screen device, uniformly sized fragments are screened out based on a preset aperture size, removing oversized or undersized particles to ensure fragment consistency and improve recycling efficiency. The output fragment is lithium iron phosphate powder, which is used to recover lithium elements.

[0047] Specifically, the recycled lithium iron phosphate batteries are removed by a robotic arm from the battery pack casing, and the copper busbars connecting the battery cells are separated. The single battery cells are taken out, and the plastic insulating film and electrode tabs are manually removed. The cells are then fed into a double-shaft shredder and coarsely crushed into 5-10 cm fragments in nitrogen to prevent the electrolyte from volatilizing and igniting. The fragments are then transferred to a hammer crusher for secondary crushing into 0.5-2 mm particles, and liquid nitrogen is sprayed simultaneously to control the temperature. The fragments are sieved through a 100-200 mesh sieve to obtain lithium iron phosphate powder.

[0048] In step S102, a mixed solution of choline chloride and 5%-20% citric acid solution is prepared in a molar ratio of 1:1, the battery scraps are leached, and reacted with the mixed solution in a solid-liquid ratio of 1:2-5, and 5-10 wt / % polymer powder catalyst is added to obtain a first filtrate and a first filter residue.

[0049] The reaction temperature is 60-80°C, the reaction time is 2-7 hours, and sulfuric acid is added after the reaction to adjust the pH to 1.0-2.0; the polymer powder catalyst is one of polycarbonate, polyethylene terephthalate or polyamide.

[0050] It is understood that the present embodiment uses choline chloride as a hydrogen bond acceptor and citric acid as a hydrogen bond donor, which are mixed in molar ratios and heated at 60–80°C to form a transparent liquid with a stable hydrogen bond network. Water is added to reduce the viscosity of the system to improve mass transfer efficiency. During the selective leaching process, chloride ions form a soluble complex with lithium chloride with lithium ions to achieve directional dissolution of lithium. At the same time, citric acid provides hydrogen ions to dissolve metal oxides and reduce high-valent metals through carboxyl groups. Chloride ions preferentially coordinate lithium ions rather than sodium and potassium ions, further enhancing selectivity and increasing the lithium ion leaching rate. The acid treatment stage activates lithium leaching and maintains a reducing environment. At low pH, citric acid preferentially precipitates trivalent iron ions, while lithium ions remain in the liquid phase due to lithium chloride complexation. The addition of a polymer catalyst allows amino and carboxyl groups to adsorb lithium ions and accelerate electron transfer, promoting the breaking of Li–O bonds in lithium iron phosphate. The negative surface charge repels high-charge density ions, selectively enriching lithium ions and further improving the leaching rate of lithium iron phosphate. The polymer powder catalyst generates a local electric field through the triboelectric effect, accelerating the detachment of lithium ions from the LiFePO4 lattice.

[0051] Specifically, lithium iron phosphate powder is activated by ball milling and then leached with citric acid before direct hydrothermal regeneration. Increasing the citric acid concentration from 5% to 20% increases the lithium ion leaching rate from 85% to 96%. Further increasing the citric acid concentration to 25% reduces the leaching rate to 89%. This is because excess citric acid forms colloidal FeCit during hydrothermal treatment, which encapsulates the lithium iron phosphate particles and hinders the reaction. Citric acid acts synergistically, and at its optimal concentration, it functions as a leaching agent, carbon source, and crystal growth regulator.

[0052] In step S103, calcium hydroxide is added to the first filtrate to adjust the pH to 4, so as to precipitate the iron ions and phosphorus ions, and the second filtrate and the second filter residue are obtained after filtration.

[0053] The iron and phosphorus contents in the first filtrate are 1 eq, and the amount of calcium hydroxide added is 1.5 eq.

[0054] In step S104, 0.1 wt / % activated carbon is added to the second filtrate to reduce the residual iron, phosphorus and other impurities in the solution to less than 1 mg / L, and a third filtrate and a third filter residue are obtained after filtration.

[0055] The reaction temperature was 40°C and the reaction time was 1 h.

[0056] It can be understood that the activated carbon in the embodiment of the present application achieves efficient adsorption decolorization and deep impurity removal by virtue of its developed pore system composed of microcrystalline carbon: the micropores account for more than 95%, and small molecular pigments and ions are adsorbed by van der Waals forces; the oxygen-containing functional groups on the surface of the activated carbon give polarity, and selectively complex metal ions through chemical adsorption or ion exchange, thereby deeply removing residual impurity ions such as sodium ions, phosphate ions, etc., while the lithium chloride complex formed by chloride ions and lithium ions is mainly retained in the liquid phase due to the size effect, and the residual metal ions are <20ppm.

[0057] Specifically, in the wet recycling of batteries, citric acid solution is used to leach lithium iron phosphate black powder. The solution contains divalent iron ions, sodium ions and sulfate ions. The low-concentration lithium iron phosphate solution is turbid and light yellow. 0.1-0.5wt / % reagent-grade activated carbon is added and reacted at 40-60°C for 2-4 hours. The lithium carbonate solution becomes clear and almost transparent. The content of iron ions, sodium ions and sulfate ions in the solution is less than 20ppm.

[0058] In step S105, hydrochloric acid is added to the third filtrate to adjust the pH to 2.0, the reaction temperature is 20°C, and the reaction time is 2 hours to obtain a lithium chloride solution.

[0059] It is understandable that in the embodiment of the present application, lithium ions react with hydrochloric acid to generate lithium chloride, which is dissolved in the solution to prepare for the carbonization step.

[0060] Specifically, lithium ions are stable cations and cannot directly react with hydrochloric acid to form lithium chloride. Instead, the reaction to form lithium chloride is a displacement reaction between metallic lithium and hydrochloric acid. As an alkali metal, metallic lithium has a strong reducing property and can undergo a redox reaction with the hydrogen ions in hydrochloric acid to form lithium chloride.

[0061] In step S106, 1 wt / % catalyst is added to the lithium chloride solution, the reaction temperature is 60° C., carbon dioxide is introduced into the lithium chloride solution at a ventilation rate of 0.05 L / min, a pressure of 6.5 MPa, and a reaction time of 18 h to obtain a lithium carbonate solution.

[0062] Wherein, the catalyst is one of triethylamine or tripropylamine.

[0063] It is understandable that the embodiment of the present application undergoes a reversible reaction between lithium chloride and carbon dioxide in an aqueous solution to generate lithium carbonate and hydrochloric acid, and this process forms a soluble salt; the carbon dioxide partial pressure is significantly increased by a high pressure of 6.5 MPa, and the gas solubility increases linearly according to Henry's law, and the concentration of liquid carbon dioxide is increased; during the carbonization process, triethylamine continuously consumes hydrogen ions to push the carbonate fractionation equilibrium to the right, significantly increasing the carbonate ion concentration and combining with lithium ions to form lithium carbonate crystal nuclei. At the same time, triethylamine preferentially complexes impurity ions such as magnesium ions and calcium ions, inhibiting their reaction with carbonate ions and improving product purity. The reaction temperature is controlled at 60°C, which can balance kinetic and thermodynamic requirements. The lower limit of 60°C is higher than the CO2 hydration activation energy to ensure the reaction rate, and the upper limit of 80°C is lower than the lithium carbonate solubility inflection point to avoid crystal dissolution; the 18-hour reaction time ensures that the crystals achieve particle size homogenization through Ostwald ripening, thereby reducing the particle size of lithium carbonate.

[0064] Specifically, 1 wt / % triethylamine was added to the lithium chloride solution, the reaction temperature was 60° C., carbon dioxide was introduced into the lithium chloride solution at a ventilation rate of 0.05-0.1 liters / minute, a pressure of 6.5 MPa, and a reaction time of 18 hours to obtain lithium carbonate crystals with uniform crystal form and a particle size of 5-10 microns.

[0065] In step S107, the lithium carbonate solution is heated to 80-100°C and kept warm for 1 hour, and then cooled in a gradient and kept warm for 1-2 hours, wherein the gradient cooling is 20°C per stage, and filtered to obtain a fourth filtrate and a fourth filter cake. The fourth filtrate is recycled according to step (6), and the fourth filter cake is pulped 3 times at a pulping temperature of 60-80°C, and filtered to obtain a high-purity lithium carbonate wet product, which is dried at 100-120°C to obtain a high-purity lithium carbonate crystal powder.

[0066] In the process, the stirring speed is controlled at 300-600 r / min, and the pure water with a particle number of ≤1 / mL is selected for the beating-up, and the drying of the lithium carbonate wet product is performed under negative pressure.

[0067] It can be understood that the embodiments of the present application precisely control the crystallization kinetics through three stages. In the high-temperature stage (80-90°C), spontaneous nucleation is inhibited, the solution is in a metastable state, and a uniform solute environment is provided; in the medium-temperature stage (25-50°C), slow cooling induces secondary nucleation, forming controllable crystal seeds, and avoiding impurity wrapping caused by explosive nucleation; in the low-temperature stage (0 to -20°C), small crystals are dissolved and re-deposited on large crystals, and sodium ions, magnesium ions and other ions have high solubility at low temperatures, while the solubility of lithium carbonate increases significantly with the decrease of temperature, realizing the separation of lithium and alkali metals and reducing impurities. The high-purity water beating-up deeply removes impurities through three mechanisms. Ion diffusion: a concentration gradient is formed at a low ion concentration, which promotes the diffusion of residual sodium ions between crystals to the water phase, and the sodium ion is <20 ppm after single washing; sulfate ions are desorbed from the crystal surface according to the Stokes-Einstein diffusion principle, and the residual sulfate ion is <20 ppm; colloid stripping: the hydrogen bonds and electrostatic adsorption between colloids such as iron hydroxide and crystals are destroyed, and the mechanical desorption is realized by 300 r / min stirring to remove iron ions; by controlling the stirring speed at 600 r / min, it is beneficial to maintain a suitable saturation concentration, reduce impurity wrapping, promote solute diffusion, and optimize the crystal morphology; using pure water for beating-up avoids the introduction of additional ions and organic impurities, and improves the purity of the finished product.

[0068] Specifically, the lithium carbonate solution is incubated at 80°C for 2h, slowly cooled to 60°C for 2h, then slowly cooled to 20°C for 2h, and finally slowly cooled to 0°C for 2h, and then filtered. The filtration obtained the crystallization filtrate and the crystallization filter cake, the crystallization filter cake was added with pure water and incubated at 60°C for 1h, and then filtered to obtain the first beating-up filtrate and the first beating-up filter cake. The first beating-up filter cake was added with pure water and incubated at 60°C for 1h, and then filtered to obtain the second beating-up filtrate and the second beating-up filter cake. The second beating-up filter cake was continuously added with pure water and incubated at 60°C for 1h, and then filtered to obtain the third beating-up filtrate and the third beating-up filter cake. The stirring speed in the whole crystallization beating-up process was controlled at 300 r / min, and the third beating-up filter cake was vacuum dried at 120°C to obtain the high-purity lithium carbonate product.

[0069] The embodiment of the application provides a method for preparing battery-grade lithium carbonate from waste lithium batteries. Choline chloride-citric acid is used as a eutectic solvent system. Chloride ions selectively complex lithium ions to form soluble lithium chloride to realize directional leaching of lithium. At the same time, citric acid provides hydrogen ions to dissolve metal oxides and reduce high-valence metals through carboxyl groups. Low-pH precipitation of trivalent iron ions retains lithium in the liquid phase. At the same time, the polymer catalyst accelerates the breaking of the Li-O bond and selectively enriches lithium ions, thereby improving the recovery rate of lithium. Activated carbon is used to remove impurities: microporous structures adsorb small molecular impurities, surface functional groups remove sodium ions and phosphate ions through chemical adsorption, and lithium chloride remains in the liquid phase due to size effects, thereby being transferred to the carbonization step. In the carbonization step, the lithium chloride solution is subjected to high pressure of 6.5 MPa. Triethylamine is used to catalyze the increase of the solubility of carbon dioxide and complex magnesium / calcium ions to inhibit impurities. The reaction is carried out at 60-80°C for 18-23 hours to combine carbonate and lithium into lithium carbonate, and the particle size is uniformized through crystal growth, thereby obtaining high-purity lithium carbonate with sodium residue of less than 20 ppm. The gradient crystallization stage adopts three-stage temperature control (80-100°C to suppress nuclei -> 40-60°C to induce crystal seeds -> 0-20°C to dissolve small crystals and separate alkali metals). The filtrate is recycled to the initial crystallization to reduce the loss of lithium yield and improve the recovery rate of lithium. The filtrate is reused in three stages and added to the crystallization mother liquor as a dilution medium. The pure water beating step deeply removes impurities through concentration gradient diffusion, colloid stripping and physical diffusion, further reducing the impurity content of the lithium carbonate product. Thus, the technical problems of low lithium ion recovery rate, complex process, low purity of lithium carbonate, large crystal size, uneven particle size and many impurities in lithium iron phosphate batteries are solved.

[0070] A method for preparing battery-grade lithium carbonate from waste lithium batteries will be described below through specific examples, including:

[0071] Example 1

[0072] The first aspect embodiment of the application provides a method for preparing battery-grade lithium carbonate from waste lithium batteries, including the following steps:

[0073] (1) The recovered lithium iron phosphate battery is disassembled, crushed and sieved to obtain battery fragments;

[0074] (2) A mixed solution of choline chloride and 5% concentration citric acid solution is prepared according to a molar ratio of 1:1. The battery fragments are leached and reacted with the mixed solution according to a solid-liquid ratio of 1:2. At the same time, 5wt% polymer powder catalyst is added to obtain a first filtrate and a first filter residue;

[0075] (3) The first filtrate is added to calcium hydroxide to adjust the pH to 4, so that iron ions and phosphorus ions are precipitated. After filtration, a second filtrate and a second filter residue are obtained;

[0076] (4) adding 0.1 wt / % activated carbon to the second filtrate to reduce the residual iron, phosphorus and other impurities in the solution to less than 1 mg / L, and filtering to obtain a third filtrate and a third filter residue;

[0077] (5) adding hydrochloric acid to the third filtrate to adjust the pH to 2.0, the reaction temperature was 20° C., and the reaction time was 2 h to obtain a lithium chloride solution;

[0078] (6) adding 1 wt / % catalyst to a lithium chloride solution, the reaction temperature was 60° C., and carbon dioxide was introduced into the lithium chloride solution at a ventilation rate of 0.05 L / min, a pressure of 6.5 MPa, and a reaction time of 18 h to obtain a lithium carbonate solution;

[0079] (7) The lithium carbonate solution is heated to 60°C and kept warm for 1 hour, and then cooled in a gradient manner and kept warm for 1 hour, wherein the gradient cooling is 20°C per stage, and filtered to obtain a fourth filtrate and a fourth filter cake, and the fourth filtrate is recycled according to step (6), and the fourth filter cake is pulped 3 times at a pulping temperature of 60°C, and filtered to obtain a high-purity lithium carbonate wet product, which is dried at 100°C to obtain a high-purity lithium carbonate crystal powder, such as Figure 2 shown.

[0080] Wherein, in step (2), the reaction temperature is 60° C., the reaction time is 2 hours, and sulfuric acid is added after the reaction is completed to adjust the pH to 2.0.

[0081] Wherein, the polymer powder catalyst is polycarbonate.

[0082] Wherein, the reaction temperature in step (4) is 40° C. and the reaction time is 1 h.

[0083] Wherein, the catalyst is triethylamine.

[0084] Wherein, the stirring speed during step (7) is controlled at 600 r / min.

[0085] Wherein, the sieving in step (1) is performed through a 100-mesh sieve.

[0086] The iron and phosphorus contents in the first filtrate are 1 eq, and the amount of calcium hydroxide added is 1.5 eq.

[0087] In the step (7), pure water with a particle number of ≤1 / mL is used for beating.

[0088] The drying of the wet lithium carbonate product in step (7) needs to be carried out under negative pressure.

[0089] The comparison of the lithium carbonate values ​​obtained in Example 1 with the requirements of the industry standard YS / T582-2013 is shown in Table 1:

[0090] Table 1: Comparison of data between Example 1 and industry standard YS / T582-2013

[0091] Indicator Value Industry Standard Lithium carbonate purity 99.91% Average 98% by wet process Overall lithium recovery 99.68% 85-90% by conventional process Sodium ion residual 18 ppm Battery grade < 100 ppm Sulphate ion residual 9 ppm Battery grade < 200 ppm Crystal size 6.45 pm Positive electrode material requirement 1-20 pm Lithium carbonate colour White White required

[0092] As shown in Table 1, after decolorization and adsorption by activated carbon, the filtrate was clarified. Figure 3 As shown, the color of the lithium carbonate finally obtained is white. Figure 2 As shown, the sulfate residue was 9 ppm, the purity was 99.91%, and the total lithium recovery rate was 99.68%.

[0093] Example 2

[0094] The first embodiment of the present application provides a method for preparing battery-grade lithium carbonate from waste lithium batteries, comprising the following steps:

[0095] (1) Disassembling, crushing, and screening the recovered lithium iron phosphate batteries to obtain battery scraps;

[0096] (2) preparing a mixed solution of choline chloride and 8% citric acid solution in a molar ratio of 1:1, leaching the battery crushed material, and reacting the mixed solution with the mixed solution in a solid-liquid ratio of 1:3, while adding 6 wt / % polymer powder catalyst to obtain a first filtrate and a first filter residue;

[0097] (3) adding calcium hydroxide to the first filtrate to adjust the pH to 4.5 to precipitate iron ions and phosphorus ions, and filtering to obtain a second filtrate and a second filter residue;

[0098] (4) Add 0.2 wt / % activated carbon to the second filtrate to make the residual iron, phosphorus and other impurities in the solution less than 1 mg / L, and filter to obtain the third filtrate, such as Figure 2 As shown, and the third filter residue;

[0099] (5) adding hydrochloric acid to the third filtrate to adjust the pH to 1.8, the reaction temperature was 30° C., and the reaction time was 2.5 h to obtain a lithium chloride solution;

[0100] (6) adding 2 wt / % catalyst to lithium chloride solution, the reaction temperature was 65° C., carbon dioxide was introduced into the lithium chloride solution at a ventilation rate of 0.06 L / min, a pressure of 6.5 MPa, and a reaction time of 19 h to obtain a lithium carbonate solution;

[0101] (7) The lithium carbonate solution was heated to 70°C and kept warm for 1 hour, and then cooled in a gradient manner and kept warm for 1.5 hours, wherein the gradient cooling was 20°C per stage, and the fourth filtrate and the fourth filter cake were obtained by filtration. The fourth filtrate was recycled according to step (6), and the fourth filter cake was pulped three times at a pulping temperature of 60°C, and high-purity lithium carbonate wet product was obtained by filtration, and dried at 110°C to obtain high-purity lithium carbonate crystal powder.

[0102] Wherein, in step (2), the reaction temperature is 65° C., the reaction time is 3 hours, and sulfuric acid is added after the reaction is completed to adjust the pH to 1.8.

[0103] Wherein, the polymer powder catalyst is polyethylene terephthalate.

[0104] Wherein, the reaction temperature in step (4) is 45° C. and the reaction time is 2 h.

[0105] Wherein, the catalyst is triethylamine.

[0106] Wherein, the stirring speed during step (7) is controlled at 500 r / min.

[0107] Wherein, the sieving in step (1) is performed through a 150-mesh sieve.

[0108] The iron and phosphorus contents in the first filtrate are 1 eq, and the amount of calcium hydroxide added is 1.6 eq.

[0109] In step (7), pure water with a particle number of ≤1 / mL is used for beating.

[0110] Wherein, the drying of the wet lithium carbonate product in step (7) needs to be carried out under negative pressure.

[0111] The comparison of the lithium carbonate values ​​obtained in Example 2 with the requirements of the industry standard YS / T582-2013 is shown in Table 2:

[0112] Table 2: Comparison of data between Example 2 and industry standard YS / T582-2013

[0113] Indicator Value Industry Standard Lithium carbonate purity 99.92% Average 98% by wet process Overall lithium recovery 99.67% 85-90% by conventional process Sodium ion residual 15 ppm Battery grade < 100 ppm Sulphate ion residual 8 ppm Battery grade < 200 ppm Crystal size 6.55 pm Positive electrode material requirement 1-20 pm Lithium carbonate colour White White required

[0114] As shown in Table 2, the total lithium recovery rate increased to 99.67% by increasing the concentration of the citric acid solution and the amount of polymer powder catalyst added.

[0115] Example 3

[0116] The first embodiment of the present application provides a method for preparing battery-grade lithium carbonate from waste lithium batteries, comprising the following steps:

[0117] (1) Disassembling, crushing, and screening the recovered lithium iron phosphate batteries to obtain battery scraps;

[0118] (2) preparing a mixed solution of choline chloride and 10% citric acid solution in a molar ratio of 1:1, leaching the battery crushed material, and reacting the mixed solution with the mixed solution in a solid-liquid ratio of 1:3.5, while adding 7 wt / % polymer powder catalyst to obtain a first filtrate and a first filter residue;

[0119] (3) adding calcium hydroxide to the first filtrate to adjust the pH to 5 to precipitate iron ions and phosphorus ions, and filtering to obtain a second filtrate and a second filter residue;

[0120] (4) adding 0.3 wt / % activated carbon to the second filtrate to reduce the residual iron, phosphorus and other impurities in the solution to less than 1 mg / L, and filtering to obtain a third filtrate and a third filter residue;

[0121] (5) adding hydrochloric acid to the third filtrate to adjust the pH to 1.6, the reaction temperature was 40° C., and the reaction time was 3 h to obtain a lithium chloride solution;

[0122] (6) adding 4 wt / % catalyst to a lithium chloride solution, the reaction temperature was 70° C., and carbon dioxide was introduced into the lithium chloride solution at a ventilation rate of 0.07 L / min, a pressure of 6.5 MPa, and a reaction time of 20 h to obtain a lithium carbonate solution;

[0123] (7) The lithium carbonate solution is heated to 70°C and kept warm for 1 hour, and then cooled in a gradient manner and kept warm for 2 hours, wherein the gradient cooling is 20°C per stage, and filtered to obtain a fourth filtrate and a fourth filter cake. The fourth filtrate is recycled according to step (6), and the fourth filter cake is pulped three times at a pulping temperature of 60°C, and filtered to obtain a high-purity lithium carbonate wet product, which is dried at 120°C to obtain a high-purity lithium carbonate crystal powder.

[0124] Wherein, in step (2), the reaction temperature is 70° C., the reaction time is 4 hours, and sulfuric acid is added after the reaction is completed to adjust the pH to 1.6.

[0125] Wherein, the polymer powder catalyst is polycarbonate.

[0126] Wherein, the reaction temperature in step (4) is 50° C. and the reaction time is 3 h.

[0127] Wherein, the catalyst is tripropylamine.

[0128] Wherein, the stirring speed during step (7) is controlled at 400 r / min.

[0129] Wherein, the sieving in step (1) is performed through a 150-mesh sieve.

[0130] The iron and phosphorus contents in the first filtrate are 1 eq, and the amount of calcium hydroxide added is 1.7 eq.

[0131] In step (7), pure water with a particle count of ≤1 particle / mL is used for beating. Furthermore, the drying of the wet lithium carbonate product in step (7) needs to be carried out under negative pressure.

[0132] The comparison of the lithium carbonate values ​​obtained in Example 3 with the requirements of the industry standard YS / T582-2013 is shown in Table 3:

[0133] Table 3: Comparison of data between Example 3 and industry standard YS / T582-2013

[0134] Indicator Value Industry Standard Lithium carbonate purity 99.93% Average 98% by wet process Overall lithium recovery 99.71% 85-90% by conventional process Sodium ion residual 12 ppm Battery grade < 100 ppm Sulphate ion residual 8 ppm Battery grade < 200 ppm Crystal size 6.40 pm Positive electrode material requirement 1-20 pm Lithium carbonate colour White White required

[0135] As shown in Table 3, compared with Example 2, Example 3 increases the concentration of citric acid, replaces the polymer powder catalyst polyethylene terephthalate with polycarbonate, and further improves the total lithium recovery rate; increases the amount of activated carbon and the reaction time, and increases the temperature and stirring speed of the gradient cooling crystallization. Ultimately, the residual sodium ions and sulfate ions are further reduced, and the purity of lithium carbonate is improved.

[0136] Example 4

[0137] The first embodiment of the present application provides a method for preparing battery-grade lithium carbonate from waste lithium batteries, comprising the following steps:

[0138] (1) Disassembling, crushing, and screening the recovered lithium iron phosphate batteries to obtain battery scraps;

[0139] (2) preparing a mixed solution of choline chloride and 12% citric acid solution in a molar ratio of 1:1, leaching the battery crushed material, and reacting the mixed solution with the mixed solution in a solid-liquid ratio of 1:4, while adding 8 wt / % polymer powder catalyst to obtain a first filtrate and a first filter residue;

[0140] (3) adding calcium hydroxide to the first filtrate to adjust the pH to 5.5 to precipitate iron ions and phosphorus ions, and filtering to obtain a second filtrate and a second filter residue;

[0141] (4) adding 0.4 wt / % activated carbon to the second filtrate to reduce the residual iron, phosphorus and other impurities in the solution to less than 1 mg / L, and filtering to obtain a third filtrate and a third filter residue;

[0142] (5) adding hydrochloric acid to the third filtrate to adjust the pH to 1.5, the reaction temperature was 50° C., and the reaction time was 3 h to obtain a lithium chloride solution;

[0143] (6) adding 4 wt / % catalyst to a lithium chloride solution, the reaction temperature was 75° C., and carbon dioxide was introduced into the lithium chloride solution at a ventilation rate of 0.08 L / min, a pressure of 6.5 MPa, and a reaction time of 21 h to obtain a lithium carbonate solution;

[0144] (7) The lithium carbonate solution is heated to 90°C and kept warm for 1 hour, and then cooled in a gradient manner and kept warm for 2 hours, wherein the gradient cooling is 20°C per stage, and filtered to obtain a fourth filtrate and a fourth filter cake. The fourth filtrate is recycled according to step (6), and the fourth filter cake is pulped three times at a pulping temperature of 70°C, and filtered to obtain a high-purity lithium carbonate wet product, which is dried at 120°C to obtain a high-purity lithium carbonate crystal powder.

[0145] Wherein, in step (2), the reaction temperature is 75° C., the reaction time is 5 hours, and sulfuric acid is added after the reaction is completed to adjust the pH to 1.5.

[0146] Wherein, the polymer powder catalyst is polycarbonate.

[0147] Wherein, the reaction temperature in step (4) is 50° C. and the reaction time is 3 h.

[0148] Wherein, the catalyst is triethylamine.

[0149] Wherein, the stirring speed during step (7) is controlled at 300 r / min.

[0150] Wherein, the sieving in step (1) is performed through a 100-mesh sieve.

[0151] The iron and phosphorus contents in the first filtrate are 1 eq, and the amount of calcium hydroxide added is 1.8 eq.

[0152] In step (7), pure water with a particle number of ≤1 / mL is used for beating.

[0153] Wherein, the drying of the wet lithium carbonate product in step (7) needs to be carried out under negative pressure.

[0154] The comparison of the lithium carbonate values ​​obtained in Example 4 with those required by the industry standard YS / T582-2013 is shown in Table 4:

[0155] Table 4: Comparison of data between Example 4 and industry standard YS / T582-2013

[0156] Indicator Value Industry Standard Lithium carbonate purity 99.95% Average 98% by wet process Overall lithium recovery 99.73% 85-90% by conventional process Sodium ion residual 9 ppm Battery grade < 100 ppm Sulphate ion residual 6 ppm Battery grade < 200 ppm Crystal size 6.35 pm Positive electrode material requirement 1-20 pm Lithium carbonate colour White White required

[0157] As shown in Table 4, compared with Example 3, Example 4 further increased the amount of polymer powder catalyst, and the total lithium recovery rate was further improved; the amount of activated carbon and the reaction time were increased, and the temperature and stirring speed of the gradient cooling crystallization were increased. Finally, the particle size of the lithium carbonate product was smaller and the purity was higher.

[0158] Example 5

[0159] The first embodiment of the present application provides a method for preparing battery-grade lithium carbonate from waste lithium batteries, comprising the following steps:

[0160] (1) Disassembling, crushing, and screening the recovered lithium iron phosphate batteries to obtain battery scraps;

[0161] (2) preparing a mixed solution of choline chloride and 15% citric acid solution in a molar ratio of 1:1, leaching the battery crushed material, and reacting the mixed solution with the mixed solution in a solid-liquid ratio of 1:4, while adding 5-10 wt / % polymer powder catalyst to obtain a first filtrate and a first filter residue;

[0162] (3) adding calcium hydroxide to the first filtrate to adjust the pH to 6 to precipitate iron ions and phosphorus ions, and filtering to obtain a second filtrate and a second filter residue;

[0163] (4) adding 0.45 wt / % activated carbon to the second filtrate to reduce the residual iron, phosphorus and other impurities in the solution to less than 1 mg / L, and filtering to obtain a third filtrate and a third filter residue;

[0164] (5) adding hydrochloric acid to the third filtrate to adjust the pH to 1.2, the reaction temperature was 60° C., and the reaction time was 3 h to obtain a lithium chloride solution;

[0165] (6) adding 4.5 wt / % catalyst to a lithium chloride solution, the reaction temperature was 80° C., and carbon dioxide was introduced into the lithium chloride solution at a ventilation rate of 0.09 L / min, a pressure of 6.5 MPa, and a reaction time of 22 h to obtain a lithium carbonate solution;

[0166] (7) The lithium carbonate solution is heated to 90°C and kept warm for 1 hour, and then cooled in a gradient manner and kept warm for 3 hours, wherein the gradient cooling is 20°C per stage, and the fourth filtrate and the fourth filter cake are obtained by filtration. The fourth filtrate is recycled according to step (6), and the fourth filter cake is pulped 3 times at a pulping temperature of 70°C, and a high-purity lithium carbonate wet product is obtained by filtration, which is then dried at 120°C to obtain a high-purity lithium carbonate crystal powder.

[0167] Wherein, in step (2), the reaction temperature is 75° C., the reaction time is 5 hours, and sulfuric acid is added after the reaction is completed to adjust the pH to 1.2.

[0168] Wherein, the polymer powder catalyst is polyamide.

[0169] Wherein, the reaction temperature in step (4) is 55° C. and the reaction time is 3 h.

[0170] Wherein, the catalyst is triethylamine.

[0171] Wherein, the stirring speed during step (7) is controlled at 300 r / min.

[0172] Wherein, the sieving in step (1) is performed through a 100-mesh sieve.

[0173] The iron and phosphorus contents in the first filtrate are 1 eq, and the amount of calcium hydroxide added is 1.8 eq.

[0174] In step (7), pure water with a particle number of ≤1 / mL is used for beating.

[0175] Wherein, the drying of the wet lithium carbonate product in step (7) needs to be carried out under negative pressure.

[0176] The comparison of the lithium carbonate values ​​obtained in Example 5 with the requirements of the industry standard YS / T582-2013 is shown in Table 5:

[0177] Table 5: Comparison of data between Example 5 and industry standard YS / T582-2013

[0178] Indicator Value Industry Standard Lithium carbonate purity 99.96% Average 98% by wet process Overall lithium recovery 99.74% 85-90% by conventional process Sodium ion residual 9 ppm Battery grade < 100 ppm Sulphate ion residual 4 ppm Battery grade < 200 ppm Crystal size 6.39 pm Positive electrode material requirement 1-20 pm Lithium carbonate colour White White required

[0179] As shown in Table 5, compared with Example 4, Example 5 further increased the concentration of citric acid and the amount of polymer powder catalyst used, replaced polycarbonate with polyamide as the polymer powder catalyst, and further improved the total lithium recovery rate; increased the reaction temperature and reaction time during the carbonization process, and improved the total lithium recovery rate.

[0180] Example 6

[0181] The first embodiment of the present application provides a method for preparing battery-grade lithium carbonate from waste lithium batteries, comprising the following steps:

[0182] (1) Disassembling, crushing, and screening the recovered lithium iron phosphate batteries to obtain battery scraps;

[0183] (2) preparing a mixed solution of choline chloride and 15% citric acid solution in a molar ratio of 1:1, leaching the battery crushed material, and reacting the mixed solution with the mixed solution in a solid-liquid ratio of 1:5, while adding 10 wt / % polymer powder catalyst to obtain a first filtrate and a first filter residue;

[0184] (3) adding calcium hydroxide to the first filtrate to adjust the pH to 6 to precipitate iron ions and phosphorus ions, and filtering to obtain a second filtrate and a second filter residue;

[0185] (4) adding 0.5 wt / % activated carbon to the second filtrate to reduce the residual iron, phosphorus and other impurities in the solution to less than 1 mg / L, and filtering to obtain a third filtrate and a third filter residue;

[0186] (5) adding hydrochloric acid to the third filtrate to adjust the pH to 1.0, the reaction temperature was 60° C., and the reaction time was 2 h to obtain a lithium chloride solution;

[0187] (6) adding 5 wt / % catalyst to lithium chloride solution, the reaction temperature is 80° C., and carbon dioxide is introduced into the lithium chloride solution at a ventilation rate of 0.1 L / min, a pressure of 6.5 MPa, and a reaction time of 23 h to obtain a lithium carbonate solution;

[0188] (7) The lithium carbonate solution is heated to 100°C and kept warm for 1 hour, and then cooled in a gradient manner and kept warm for 2 hours, wherein the gradient cooling is 20°C per stage, and filtered to obtain a fourth filtrate and a fourth filter cake. The fourth filtrate is recycled according to step (6), and the fourth filter cake is pulped three times at a pulping temperature of 80°C, and filtered to obtain a high-purity lithium carbonate wet product, which is dried at 110°C to obtain a high-purity lithium carbonate crystal powder.

[0189] Wherein, in step (2), the reaction temperature is 80° C., the reaction time is 5 hours, and sulfuric acid is added after the reaction is completed to adjust the pH to 1.0.

[0190] Wherein, the polymer powder catalyst is polycarbonate.

[0191] Wherein, the reaction temperature in step (4) is 60° C. and the reaction time is 3 h.

[0192] Wherein, the catalyst is tripropylamine.

[0193] Wherein, the stirring speed during step (7) is controlled at 300 r / min.

[0194] Wherein, the sieving in step (1) is performed through a 100-mesh sieve.

[0195] The iron and phosphorus contents in the first filtrate are 1 eq, and the amount of calcium hydroxide added is 2.0 eq.

[0196] In step (7), pure water with a particle number of ≤1 / mL is used for beating.

[0197] Wherein, the drying of the wet lithium carbonate product in step (7) needs to be carried out under negative pressure.

[0198] The comparison of the lithium carbonate values ​​obtained in Example 6 with the requirements of the industry standard YS / T582-2013 is shown in Table 6:

[0199] Table 6: Comparison of data between Example 6 and industry standard YS / T582-2013

[0200]

[0201]

[0202] As shown in Table 6, compared with Example 5, Example 6 further increased the concentration of citric acid and the amount of polymer powder catalyst used, and the total lithium recovery rate was further improved; the total lithium recovery rate was reduced by replacing triethylamine in the carbonization process with tripropylamine.

[0203] Example 7

[0204] The first embodiment of the present application provides a method for preparing battery-grade lithium carbonate from waste lithium batteries, comprising the following steps:

[0205] (1) Disassembling, crushing, and screening the recovered lithium iron phosphate batteries to obtain battery scraps;

[0206] (2) preparing a mixed solution of choline chloride and 20% citric acid solution in a molar ratio of 1:1, leaching the battery crushed material, and reacting the mixed solution with the mixed solution in a solid-liquid ratio of 1:5, while adding 10 wt / % polymer powder catalyst to obtain a first filtrate and a first filter residue;

[0207] (3) adding calcium hydroxide to the first filtrate to adjust the pH to 6 to precipitate iron ions and phosphorus ions, and filtering to obtain a second filtrate and a second filter residue;

[0208] (4) adding 0.5 wt / % activated carbon to the second filtrate to reduce the residual iron, phosphorus and other impurities in the solution to less than 1 mg / L, and filtering to obtain a third filtrate and a third filter residue;

[0209] (5) Add hydrochloric acid to the third filtrate to adjust the pH to 1.0, the reaction temperature is 60°C, and the reaction time is 4 hours to obtain a lithium chloride solution;

[0210] (6) adding 5 wt / % catalyst to lithium chloride solution, the reaction temperature is 80° C., and carbon dioxide is introduced into the lithium chloride solution at a ventilation rate of 0.1 L / min, a pressure of 6.5 MPa, and a reaction time of 23 h to obtain a lithium carbonate solution;

[0211] (7) The lithium carbonate solution is heated to 100°C and kept warm for 1 hour, and then cooled in a gradient manner and kept warm for 2 hours, wherein the gradient cooling is 20°C per stage, and filtered to obtain a fourth filtrate and a fourth filter cake. The fourth filtrate is recycled according to step (6), and the fourth filter cake is pulped three times at a pulping temperature of 80°C, and filtered to obtain a high-purity lithium carbonate wet product, which is dried at 120°C to obtain a high-purity lithium carbonate crystal powder.

[0212] Wherein, in step (2), the reaction temperature is 80° C., the reaction time is 7 hours, and sulfuric acid is added after the reaction is completed to adjust the pH to 1.0.

[0213] Wherein, the polymer powder catalyst is polycarbonate.

[0214] The reaction temperature in step (4) is 60°C, and the reaction time is 3h.

[0215] The catalyst is triethylamine.

[0216] The stirring speed in step (7) is controlled at 300r / min.

[0217] The sieving in step (1) is performed through a 100-mesh sieve.

[0218] The iron and phosphorus contents in the first filtrate are 1eq, and the amount of calcium hydroxide added is 2.0eq.

[0219] The slurry in step (7) is prepared using pure water with a particle count of ≤1 / mL.

[0220] The drying of the lithium carbonate wet product in step (7) is performed under negative pressure.

[0221] The lithium carbonate obtained in Example 7 is compared with the requirements of the industry standard YS / T582-2013, as shown in Table 7:

[0222] Table 7: Comparison of data between Example 7 and the requirements of the industry standard YS / T582-2013

[0223] Indicator Value Industry Standard Lithium carbonate purity 99.95% Average 98% by wet process Overall lithium recovery 99.74% 85-90% by conventional process Sodium ion residual 8 ppm Battery grade < 100 ppm Sulphate ion residual 3 ppm Battery grade < 200 ppm Crystal size 6.29 pm Positive electrode material requirement 1-20 pm Lithium carbonate colour White White required

[0224] As shown in Table 7, compared with Example 6, in Example 7, the catalyst tripropylamine is replaced with triethylamine under the same carbonation reaction conditions, the total lithium recovery rate is improved, the drying temperature of the lithium carbonate wet product is increased, the lithium carbonate crystal particle size is reduced, and the crystal particle size is 6.29μm, as shown in Table 7. Figure 4

[0225] Example 8

[0226] The first aspect of the present application provides a method for preparing battery-grade lithium carbonate from waste lithium batteries, comprising the following steps:

[0227] (1) The recovered lithium iron phosphate battery is disassembled, crushed, and sieved to obtain battery fragments;

[0228] (2) A mixed solution of choline chloride and 20% citric acid solution is prepared according to a molar ratio of 1:1, the battery fragments are leached, and the mixed solution is reacted with the battery fragments according to a solid-liquid ratio of 1:5, while adding 10wt% polymer powder catalyst, to obtain a first filtrate and a first filter residue;

[0229] (3) The first filtrate is added to calcium hydroxide to adjust the pH to 6, so that the iron ions and phosphorus ions are precipitated, and after filtration, a second filtrate and a second filter residue are obtained;

[0230] ​(4) adding 0.5 wt / % activated carbon to the second filtrate to reduce the residual iron, phosphorus and other impurities in the solution to less than 1 mg / L, and filtering to obtain a third filtrate and a third filter residue at 5 wt / % respectively;

[0231] (5) adding hydrochloric acid to the third filtrate to adjust the pH to 1.0, the reaction temperature was 60° C., and the reaction time was 4 h to obtain a lithium chloride solution;

[0232] (6) adding a lithium chloride solution to the catalyst, the reaction temperature is 80° C., and carbon dioxide is introduced into the lithium chloride solution at a ventilation rate of 0.1 L / min, a pressure of 6.5 MPa, and a reaction time of 23 h to obtain a lithium carbonate solution;

[0233] (7) The lithium carbonate solution is heated to 100°C and kept warm for 1 hour, and then cooled in a gradient manner and kept warm for 2 hours, wherein the gradient cooling is 20°C per stage, and filtered to obtain a fourth filtrate and a fourth filter cake. The fourth filtrate is recycled according to step (6), and the fourth filter cake is pulped three times at a pulping temperature of 80°C, and filtered to obtain a high-purity lithium carbonate wet product, which is dried at 120°C to obtain a high-purity lithium carbonate powder.

[0234] Wherein, in step (2), the reaction temperature is 80° C., the reaction time is 7 hours, and sulfuric acid is added after the reaction is completed to adjust the pH to 1.0.

[0235] Wherein, the polymer powder catalyst is polyamide.

[0236] Wherein, the reaction temperature in step (4) is 60° C. and the reaction time is 3 h.

[0237] Wherein, the catalyst is triethylamine.

[0238] Wherein, the stirring speed during step (7) is controlled at 300 r / min.

[0239] Wherein, the sieving in step (1) is performed through a 100-mesh sieve.

[0240] The iron and phosphorus contents in the first filtrate are 1 eq, and the amount of calcium hydroxide added is 2.0 eq.

[0241] In step (7), pure water with a particle number of ≤1 / mL is used for beating.

[0242] Wherein, the drying of the wet lithium carbonate product in step (7) needs to be carried out under negative pressure.

[0243] The comparison of the lithium carbonate values ​​obtained in Example 8 with those required by the industry standard YS / T582-2013 is shown in Table 8.

[0244] Table 8: Comparison of data between Example 8 and industry standard YS / T582-2013

[0245] Indicator Value Industry Standard Lithium carbonate purity 99.96% Average 98% by wet process Overall lithium recovery 99.75% 85-90% by conventional process Sodium ion residual 4 ppm Battery grade < 100 ppm Sulphate ion residual 3 ppm Battery grade < 200 ppm Crystal size 6.28 pm Positive electrode material requirement 1-20 pm Lithium carbonate colour White White required

[0246] As shown in Table 8, compared with Example 6, under the same reaction conditions, in Example 7, the polymer powder was replaced by polyamide from polycarbonate, and the final total lithium recovery rate and lithium carbonate purity were reduced.

[0247] Compared with Examples 1-5, Example 6 improves its ability as a hydrogen bond donor by increasing the amount of citric acid, while increasing the reaction temperature to effectively reduce the viscosity of the system and enhance the mass transfer efficiency; the hydrogen ions released by citric acid can dissolve metal oxides, and its carboxyl groups further reduce high-valent metal ions; in addition, chloride ions preferentially complex with lithium ions, significantly inhibiting the leaching of impurities such as sodium and potassium. Multiple synergistic mechanisms ultimately achieve a simultaneous increase in lithium ion leaching rate and recovery rate.

[0248] Compared with Example 3, Example 4 raises the temperature to 90°C in the gradient crystallization step, while Example 3 is 70°C. The abnormal solubility of lithium carbonate in water is utilized, and the solubility decreases when the temperature increases, which significantly increases the supersaturation of lithium ions and strengthens the driving force for crystallization, thereby increasing the yield to 99.73%. At the same time, the solubility of coexisting impurities remains high at high temperatures, much higher than that of lithium carbonate, so more of them are retained in the mother liquor, greatly reducing the risk of co-precipitation, reducing the sodium impurity content of the product to 7ppm, and significantly improving the purity. In addition, the high temperature environment of 90°C accelerates ion diffusion, promotes the orderly arrangement of the lithium carbonate lattice, and forms denser crystals such as Figure 4 As shown, lattice defects and impurity inclusions are effectively reduced, further improving the crystallization efficiency.

[0249] Compared with Example 6, under the conditions of consistent carbonization reaction temperature, time and carbon dioxide flow rate, the catalyst is replaced by tripropylamine with triethylamine. Relying on the short alkyl chain characteristics of triethylamine, the coordination accessibility of nitrogen atoms to lithium ions is significantly improved, and the formation of carbamate intermediates is efficiently promoted. At the same time, the boiling point of triethylamine is 89 ° C, which is closer to the reaction temperature of 80 ° C. The rapid diffusion of volatile components can construct a high-concentration catalytic microenvironment at the gas-liquid interface. However, tripropylamine has a high boiling point of 156 ° C, which leads to molecular diffusion hysteresis and limited reaction activity. Ultimately, the triethylamine catalytic system increases the lithium carbonate yield to 99.75%, while the tripropylamine system only has 99.72%.

[0250] Example 8 Compared with Example 7, under the same reaction conditions, the polymer powder is replaced by polycarbonate with polyamide. Although polycarbonate can promote the leaching of lithium ions through hydrogen bonds, the carbonate groups in its molecular chain will simultaneously trigger the non-selective leaching of sodium ions in the lithium iron phosphate battery scraps, and the acidic substances produced by the hydrolysis of polycarbonate will corrode the ion transmission channel; while the amide groups in the polyamide molecules can specifically bind to lithium ions through Lewis acid-base coordination, significantly reducing the Li +The solvation energy of the polyamide is increased, while the hydrogen bonding network formed by the carboxyl groups and anions disrupts the polyamide's crystalline structure, increasing its free volume and promoting dissolution and diffusion. This dual mechanism—selective adsorption and lattice relaxation—increases the lithium ion migration rate of the polyamide system by 2.3 times, ultimately increasing the lithium recovery rate from 99.74% in Example 7 to 99.75% in Example 8.

[0251] It can be seen from the above specific embodiments that after the lithium iron phosphate battery is disassembled and crushed, a lithium iron phosphate fragment with a smaller particle size can be obtained by passing it through a 100-mesh sieve, which is beneficial to the subsequent leaching process of the choline chloride-citric acid mixed solution; in the leaching stage, a mixed solution prepared by choline chloride and 20% citric acid solution in a 1:1 ratio is used, 10wt% polyamide is added, and the pH of the system is adjusted to 1 with sulfuric acid, thereby achieving efficient selective leaching of lithium ions, while significantly inhibiting the dissolution of impurity ions such as iron and sodium; adjusting the pH of the leachate to 6 with calcium hydroxide can maximize the precipitation and removal of iron ions and phosphate ions; adding 0.5wt% activated carbon can make the filtrate clear in color. The method comprises the following steps: adding 5 wt% triethylamine to the lithium chloride solution, introducing carbon dioxide at a flow rate of 0.1 L / min at 80° C. and a pressure of 6.5 MPa to react for 23 hours, and obtaining the highest yield of lithium carbonate; heating the obtained lithium carbonate slurry to 100° C., keeping the temperature for 1 hour, and then cooling the temperature by a gradient of 20° C. for 2 hours at each stage, and filtering to obtain a fourth filter cake; and finally slurrying and washing the filter cake three times with pure water at 80° C. and filtering to obtain a lithium carbonate product with the highest purity.

[0252] The obtained lithium carbonate element content ratio is as follows:

[0253] Table 9: Lithium carbonate element content ratio

[0254]

[0255] As shown in Table 9, compared with Examples 1-4, Example 5 improves its ability as a hydrogen bond donor by increasing the amount of citric acid. The hydrogen ions released by citric acid can dissolve metal oxides, and its carboxyl groups further reduce high-valent metal ions. In addition, chloride ions preferentially complex with lithium ions, significantly inhibiting the leaching of impurities such as sodium and potassium. Multiple synergistic mechanisms ultimately increase the lithium ion content, and the impurities are also lower than those in Examples 1-4. Compared with Example 7, Example 8 replaces the polymer powder with polycarbonate by polyamide under the same reaction conditions. Since polycarbonate will simultaneously induce non-selective leaching of sodium ions in lithium iron phosphate battery scraps, the sodium ion content in the final lithium carbonate product is higher than that in Example 8. Compared with Example 3, Example 4 raises the temperature to 90°C in the gradient crystallization step. The anomalous solubility characteristics of lithium carbonate in water are utilized. The solubility decreases when the temperature increases, which significantly increases the supersaturation of lithium ions. Therefore, the proportion of lithium ions in the finished lithium carbonate product is relatively high. At the same time, the solubility of coexisting impurities remains high at high temperatures, much higher than that of lithium carbonate, so more of them are retained in the mother liquor, greatly reducing the risk of coprecipitation. The content of sodium ions and iron ions in lithium carbonate is also lower than that in Example 3.

[0256] The present application provides a method for preparing battery-grade lithium carbonate from waste lithium batteries. Choline chloride-citric acid is used as a low eutectic solvent system. Chloride ions selectively complex lithium ions to form soluble lithium chloride to achieve directional lithium leaching. At the same time, citric acid provides hydrogen ions to dissolve metal oxides and reduce high-valent metals through carboxyl groups. Trivalent iron ions are precipitated at low pH while lithium remains in the liquid phase. At the same time, a polymer catalyst accelerates the breakage of Li-O bonds and selectively enriches lithium ions, thereby improving the recovery rate of lithium. Activated carbon is simultaneously used for deep impurity removal: the microporous structure adsorbs small molecular impurities, and the surface functional groups remove sodium ions, phosphate ions, etc. through chemical adsorption. Lithium chloride remains in the liquid phase due to the size effect, thereby turning to the decarbonization step. In the conversion step, the lithium chloride solution is catalyzed by triethylamine under a high pressure of 6.5MPa to increase the solubility of CO2, and complex magnesium / calcium ions to suppress impurities. The reaction is carried out at 60-80℃ for 18-23 hours to combine carbonate ions with lithium to form lithium carbonate, and the particle size is uniformed through crystal growth, thereby obtaining high-purity lithium carbonate with a sodium residue of <20ppm. The gradient crystallization step adopts three-stage temperature control, and the filtrate is recycled to the initial crystallization to reduce the loss of lithium yield and improve the lithium recovery rate. The three-time beating filtrate is recycled in stages and added to the crystallization mother liquor as a dilution medium. The pure water beating step further reduces the impurity content in the lithium carbonate product through concentration gradient diffusion, colloidal stripping and physical diffusion deep impurity removal. As a result, the technical problems of low lithium ion recovery rate, complex process, low purity of lithium carbonate, large crystal particle size, uneven particle size, and many impurities in lithium iron phosphate batteries are solved.

[0257] Although the embodiments of the present application have been shown and described above, it is understood that the above-described embodiments are exemplary and are not to be construed as limiting the present application, and that variations, modifications, substitutions and changes can be made by those skilled in the art without departing from the scope of the present application.

Claims

1. A method for preparing battery-grade lithium carbonate from waste lithium batteries, characterized in that: The following steps are involved: (1) Disassembling, crushing, and screening the recovered lithium iron phosphate batteries to obtain battery scraps; (2) preparing a mixed solution of choline chloride and 5%-20% citric acid solution in a molar ratio of 1:1, leaching the battery crushed material, and reacting the mixed solution with the mixed solution in a solid-liquid ratio of 1:2-5, while adding 5-10 wt / % polymer powder catalyst to obtain a first filtrate and a first filter residue; (3) adding calcium hydroxide to the first filtrate to adjust the pH to 4-6 to precipitate iron ions and phosphorus ions, and filtering to obtain a second filtrate and a second filter residue; (4) adding 0.1-0.5 wt / % activated carbon to the second filtrate to reduce the residual iron, phosphorus and other impurities in the solution to less than 1 mg / L, and filtering to obtain a third filtrate and a third filter residue; (5) adding hydrochloric acid to the third filtrate to adjust the pH to 1.0-2.0, the reaction temperature is 20-60° C., and the reaction time is 2-4 h to obtain a lithium chloride solution; (6) adding 1-5 wt / % of a catalyst to the lithium chloride solution, the reaction temperature is 60-80° C., and carbon dioxide is introduced into the lithium chloride solution at a ventilation rate of 0.05-0.1 liter / minute, a pressure of 6.5 MPa, and a reaction time of 18-23 hours to obtain a lithium carbonate solution; (7) The lithium carbonate solution is heated to 80-100°C and kept warm for 1 hour, and then cooled in a gradient manner and kept warm for 1-2 hours, wherein the gradient cooling is performed at a rate of 20°C per stage, and a fourth filtrate and a fourth filter cake are obtained by filtration. The fourth filtrate is recycled according to step (6), and the fourth filter cake is pulped three times at a pulping temperature of 60-80°C, and a high-purity lithium carbonate wet product is obtained by filtration, which is then dried at 100-120°C to obtain a high-purity lithium carbonate powder.

2. The method for preparing battery-grade lithium carbonate from waste lithium batteries according to claim 1, wherein: In the step (2), the reaction temperature is 60-80° C., the reaction time is 2-7 hours, and sulfuric acid is added after the reaction is completed to adjust the pH to 1.0-2.

0.

3. The method for preparing battery-grade lithium carbonate from waste lithium batteries according to claim 1, wherein: The polymer powder catalyst is one of polycarbonate, polyethylene terephthalate or polyamide.

4. The method for preparing battery-grade lithium carbonate from waste lithium batteries according to claim 1, wherein: In the step (4), the reaction temperature is 40-60° C. and the reaction time is 1-3 h.

5. The method for preparing battery-grade lithium carbonate from waste lithium batteries according to claim 1, wherein: The catalyst is one of triethylamine or tripropylamine.

6. The method for preparing battery-grade lithium carbonate from waste lithium batteries according to claim 1, wherein: During step (7), the stirring speed is controlled at 300-600 r / min.

7. The method for preparing battery-grade lithium carbonate from waste lithium batteries according to claim 1, wherein: In the step (7), pure water with a particle number of ≤1 / mL is used for beating.

8. The method for preparing battery-grade lithium carbonate from waste lithium batteries according to claim 1, wherein: The drying of the wet lithium carbonate product in step (7) needs to be carried out under negative pressure.

9. The method for preparing battery-grade lithium carbonate from waste lithium batteries according to claim 1, wherein: In the step (1), the sieve is sieved through a 100-200 mesh sieve.

10. The method for preparing battery-grade lithium carbonate from waste lithium batteries according to claim 1, wherein: The iron and phosphorus contents in the first filtrate are 1 eq, and the amount of calcium hydroxide added is 1.5-2.0 eq.

Citation Information

Cited By

  • Process for synthesizing high-crystallinity lithium carbonate through photocatalysis-assisted carbonization of waste battery lixivium

    CN122144767A